Immunohistochemical evaluation of mucin expression in precancerous tissue of stomach - Vernygorodskyi S. (Experimental Oncology, 2013)
Aim - to assess the profile of mucins (MUC1, MUC2, MUC5AC) in gastric mucosa through immunohistochemical method. To identify metaplastic areas in gastric mucosa there was used chromoendoscopy with 0,5 % solution of methylene blue, the expression of the mucins profile was determined using immunohistochemistry with MUC1, MUC5AC, MUC2 and MUC6 antibodies (clone Ma695, clone CLH2, Ccp58 and CLH5, "Novocastra" Great Britain). In case of the complete intestinal metaplasia (IM) there was maximum MUC2 expression in goblet cells. MUC5AC, MUC1 and MUC6 expression were absent in columnar epitheliocytes with brush border. In case of incomplete IM along with positive MUC2 marking of goblet cells, in 25 % of such patients with chronic atrophic gastritis with incomplete IM MUC5AC expression has been observed; but in columnar epitheliocytes MUC5AC expression was observed in 100 % of patients, and MUC2 expression was detected in 15 % of patients only. Weak expression of MUC2 and MUC5AC in the areas adjacent to gastric adenocarcinoma was registered. Key Words: mucins, precancerous changes, gastric mucosa.